2017
DOI: 10.1080/0145935x.2017.1316664
|View full text |Cite
|
Sign up to set email alerts
|

Junior high school students’ use of their afterschool hours in Ghana: The role of household assets

Abstract: Studies have examined a broad range of factors for how students use their time, but few attempts have been made to explore the nuanced link between different types of asset ownership and students'use of study time, particularly in resource-limited countries. This study uses data from junior high school students in Ghana to examine how students spend their time after school hours, the predictive influence of different types of household assets, and the extent to which these trends and relationships vary by gend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…The emphasis on academic pursuits by Pakistani youth overall reflects the value placed on education given the socioeconomic context of Pakistan. This is consistent with the developmental asset patterns found in other Asian and African countries (Alhassan et al., 2017; Amin & Chandrasekhar, 2012; Chen & Lu, 2009; Savahl et al., 2020), where a strong commitment to learning and achievement motivation was considered an (internal) asset for PYD (Scales et al., 2016). Positive educational attitudes are particularly important for youth in developing countries, as education has been shown to be one of the most effective ways to achieve intergenerational social mobility and to live a productive life (Larson & Verma, 1999).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The emphasis on academic pursuits by Pakistani youth overall reflects the value placed on education given the socioeconomic context of Pakistan. This is consistent with the developmental asset patterns found in other Asian and African countries (Alhassan et al., 2017; Amin & Chandrasekhar, 2012; Chen & Lu, 2009; Savahl et al., 2020), where a strong commitment to learning and achievement motivation was considered an (internal) asset for PYD (Scales et al., 2016). Positive educational attitudes are particularly important for youth in developing countries, as education has been shown to be one of the most effective ways to achieve intergenerational social mobility and to live a productive life (Larson & Verma, 1999).…”
Section: Discussionsupporting
confidence: 85%
“…Considering rurality of living, findings from the Young Lives cohort study in Ethiopia, India, Peru, and Vietnam showed that in comparison to youth in urban areas, rural youth spent longer hours working and less time on education (Espinoza‐Revollo & Porter, 2018). Country‐specific studies confirm that within LMICs, socioeconomic factors such as household poverty, parental education, and school enrollment significantly determine how children and youth use their time outside school (Alhassan et al., 2017; Amin & Chandrasekhar, 2012). Overall, research shows that OST varies between and within LMICs.…”
Section: Introductionmentioning
confidence: 99%
“…To better understand the influence of assets on myriad outcomes, scholars draw from asset theory to explain how assets influence behavior, attitudes, and future-oriented perspectives (Johnson and Sherraden 2007;Sherraden et al 2004). Asset theory supports the expectation that access to a savings account early in life will enable families to not only afford education expenses (e.g., transportation, school supplies, afterschool lessons; Alhassan et al 2017;Malkus et al 2017;Pallegedara and Mottaleb 2018) but also view education as an investment in their children's well-being and future. In cases where financial assets have been accumulated and saved over a long period, the assets might be sufficient to generate returns that enable families to more easily increase their school-related consumption (e.g., paying for higher education).…”
Section: Theoretical and Empirical Backgroundmentioning
confidence: 98%
“…For instance, studies conducted in Ghana and Uganda have found a negative association between agricultural assets (e.g., land and livestock ownership) and child outcomes because such assets take children away from attending school and completing schoolwork . Using data from 135 Ghanaian students, Alhassan et al (2017) found that in some rural settings, some young people have little option but to divide their afterschool time between working on homework and assisting parents on the farm. Although much of the prior work has shown the positive effects of parent and family economic resources on child outcomes, what remains unknown is whether asset holding by students themselves will improve their level of school engagement.…”
Section: Assets and Student Engagementmentioning
confidence: 99%